Concentration of blood lead and ethnicity in the United Kingdom. Issue 12 (December 1996) - Kolev, S T; House, I; Bell, G; Shaw, D; Murray, V
Abstract : The relation between concentration of blood lead and ethnic background in 779 children was examined with the analytical results from the trace element service at the Medical Toxicology Unit (MTU), Guy's and St Thomas's Hospital Trust for the period 1980-94. The ethnic identity was determined with the first and the second names of the investigated subjects. Of the patients of European origin (European) studied 72.8% v only 50.6% of the children with origins in the Indian subcontinent (Asian) had a concentration of blood lead < 100 micrograms/l. The percentage of subgroups with concentrations above the upper acceptable limit of 200 micrograms/l was significantly higher in Asian subjects (European 5% v Asian 26.5%), with the most pronounced difference in those with concentrations of blood lead of 500 micrograms/l (European 0.8% v Asian 10.5%). This study shows that a correlation exists between Asian ethnic background and concentration of blood lead in children. Factors such as cultural habits-for example, use of traditional remedies, cosmetics, diet- and socioeconomic status, may have contributed to this results.